Mao. 19 - Takahashi, Rumiko, 1957-; Garrity, Shaenon K. (Shōnen Sandē komikkusu., 2025)
"When Nanoka is transported back in time to a supernatural early 20th century, she gets recruited by aloof exorcist Mao. What thread of fate connects them? Together, they seek answers...and kick some demon butt along the way! Nanoka and Mao are obliged to work with their enemy Sasuga to save a young woman from being sacrificed to a mysterious water god. Then, the cat demon Byoki attacks one of Mao's allies! Plus, Natsuno brings Nanoka a new training challenge, an ancient, mummified man with a major grudge... "--